Perancangan Visual Branding untuk Meningkatkan Identitas dan Daya Saing UMKM Binaan Otorita Ibu Kota Nusantara (IKN) - Sary, Kezia Arum; Boer, Kheyene Molekandella; Agustian, Jaka Farih; Sanjaya, Muhammad Nurdin; Maudi, Muthia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
This community service aims to make a real contribution to the development and empowerment of Micro, Small and Medium Enterprises (MSMEs) which are members of Ibu Kota Nusantara (IKN) development program through visual branding design. The focus of this service is on increasing the identity and competitiveness of MSMEs through strong and attractive visual elements. The service method will involve collaboration between researchers, designers and MSMEs assisted by the IKN Authority. The steps include an in-depth analysis of the business characteristics and values ​​of MSMEs, as well as the development of a visual branding strategy that suits their local identity and business goals. Furthermore, training will be carried out for MSME owners regarding the implementation and maintenance of the visual identity that has been designed.